Estimating the New Keynesian Phillips Curve: A vertical production chain approach - Adam Hale Shapiro (Federal Reserve Bank of Boston, 2006)
It has become customary to estimate the New Keynesian Phillips Curve (NKPC) with GMM using a large instrument set that includes lags of variables that are ad hoc to the model. Researchers have also conventionally used real unit labor cost (RULC) as the proxy for real marginal cost, even though it is difficult to support its significance. This paper introduces a new proxy for the real marginal cost term as well as a new instrument set, both of which are based on the micro foundations of the vertical chain of production. I find that the new proxy, based on input prices as opposed to wages, provides a more robust and significant fit to the model. Instruments that are based on the vertical chain of production appear to be both more valid and relevant towards the model.
Keywords: C2; C5; E5; E3; 330